As Efektivitas Pembelajaran Daring Menggunakan Google Meet dan Whatsapp Group untuk Meningkatkan Hasil Belajar Matematika Selama Pandemi Covid 19 - Achmad Fatkhur rozi; Inqidloatul Amaniyah; Ika Rahmawati; Siti Lailiyah (MODELING: Jurnal Program Studi PGMI, 2021)
As long as pandemic Covid-19 all about learning will use online learning. This policies set by our Government to cut deployment virus Covid-19. So, altough pandemic staying we can do online learning. Many media online learning will can use by us, such as Google Meet and whatsapp grup. Both of this media can be alternative as online learning on going. Google Meet will help teachers and students face to face so, teachers can be easier to give theory. Whatsapp grup will help students for send their duty that given by teachers. So this study aims to find out how effectiveness online learning use Google Meet and whatsapp grup to increase learning outcomes mathematic during pandemic Covid-19. This study will run in Elementary School Surabaya. The research method use a quantitative method, is a method how big influence free variable to banded variable. Recruitment data collection use questionnare made by google form that given by selected correspondence. So with this study will get results about online learning use Google Meet and whatsapp grup to increase learning outcomes in only when students got theory and duty by teachers during pandemic Covid-19.